CRIMINAL POLICY IN MINOR INFRACTORS. PREVENTION OF CRIMINAL BEHAVIORS IN SPAIN TAKING AS A REFERENCE THE UNITED NATIONS GUIDELINES (RIAD GUIDELINES) - Mompeán Caballero, Lourdes (2023)
Each society is governed by a series of norms and rules that guide the way of relating and that allow citizens a protection system, ensuring life together. The guarantee of its fulfillment implies the security and stability of the company itself. On the other hand, the breach of this normative code implies a series of legal consequences. In the case of juvenile delinquency in Spain, Organic Law 5/2000 regulates the criminal responsibility of minors, specifically the period between 14 and 18 years, constituting a specific treatment for adolescents who commit crimes. However, it is important to emphasize the fact that a preventive system and therefore “pre-crime” will be preferable to the correction of the criminal act, thus preventing the deterioration of the company itself. For this, it is important, in addition to the punitive consequences governed by law, to establish a network system that covers the social and educational field as fundamental elements for prevention. Starting from the idea of prevention as a main measure in the development of adolescent behavior, it is intended to assess and propose posible alternatives and ways to improve the situation of these young people at risk, following the guidelines set by the United Nations on the prevention of juvenile delinquency, analyzing their adaptation in the Spanish socio-educational framework.